Regulation of the SOS response analyzed by RecA protein amplification. - Calsou, P (1985)
A split UV light dose procedure was used in Escherichia coli to induce an SOS function, RecA protein amplification, which was measured by an immunoradiometric assay. The SOS system was partially induced after the first UV irradiation, and the inducing effects of subsequent identical UV doses were quantified. Variations in the inducing effects of successive UV doses were related to modulations of the SOS signal level during SOS induction. A reduction in the level of SOS signal was found after 20 min in the wild-type strain, hypothesized to result from negative control of repair functions. A few DNA repair mutants were tested by the same procedure; the uvrA, recF, and umuC genes were involved in SOS induction control, but we found differences in their respective kinetics of expression. On the contrary, in a recB mutant, only a slight effect was obtained on this control.